WORD-FORMATION PROCESSES OF MEDICAL LEXICAL ITEMS IN THE JAKARTA POST’S ARTICLES - Nurmadani, Afri Tamara (Sanata Dharma University, Yogyakarta, 2022)
The understanding of medical lexical items needs to be improved in society to make people know and aware of their health issues in their daily life. This research focused on the morphology phenomenon, especially the word-formation process that happened in The Jakarta Post’s articles. This research aims to know the formation of medical lexical items that appear in the articles. The data was collected from The Jakarta Post’s articles, especially articles related to health topics. The data were classified into several types of word-formation based on the theory from Bauer (1983 2003), which supported by (Yule (2006). The researcher used a qualitative approach, specifically document analysis in analyzing the data. There are two questions in this research, which are (1) What word-formation processes of medical lexical items are involved in The Jakarta Post articles?, (2). How are the medical lexical items formed in The Jakarta Post articles?. Through this analysis, it was found eight types of word-formation which were involved in the articles related to health. It was found 165 lexical items in 11 articles. They are 10.9% for compounding, 47.3% for derivation, 3.0 % for blending, 7.3% for abbreviation and acronym, 12.1% for borrowing, 17.0% for inflection, 0,6% for back-formation, and 1.8% is clipping. The researcher hopes that it can help people to understand more about medical lexical items and the word-formation process.